ANALISIS SIFAT FISIK MATERIAL PERKERASAN JALAN HASIL DAUR ULANG - Setiawan, Hendra; Pradani, Novita (JOURNAL TEKNIK SIPIL DAN INFRASTRUKTUR, 2013)
Pavement recycling is one of resources conservation and preservation methods. Using of Reclaimed Asphalt Pavement (RAP) can give contribution to pavement quality because its quality reduction possibility due to over load of vehicle in lifetime service. For that reason, RAP physical properties research would be taken. This research using aggregat and bitumen which is come from RAP extraction. Aggregat testing such as Impact Value (AIV) test, Aggregat Pressure Value (APV) test and Spesific gravity test. Bitumen testing are penetration test, softening point test and Spesific gravity test. According to the research result, was found that RAP aggregat can be used as a pavement material. The fact can be figure out from AIV value is about 6,6% and ACV value is 20,4%. Otherwise RAP aggregat gradation is not fulfill the specification, so that gradation modified must be taken. RAP bitumen testing showing that penetration value is 21,6 dmm and softening point value is 57°C. It means that adding modifier or rejuvenating agent is necessary to do to increase quality of RAP bitumen Keywords: RAP aggregate, RAP bitumen, recycling